167 MSC-Concentrated Supernatant: A Novel Therapeutical Approach in Inflammation-Induced Preterm Brain Injury?. (October 2012) - Drommelschmidt, K; Prager, S; Bendix, I; Keller, M; Horn, PA; Ludwig, AK; Radtke, S; Giebel, B; Felderhoff-Müser, U
Abstract : Background and aims: Preterm brain injury of premature born infants is a main cause of disability and represents an enormous individual, familial and social burden. Up to 50% of these children suffer from disabilities such as cerebral palsy and cognitive disorders. The aetiology of brain injury has been considered to be multi-factorial. Factors such as hyperoxia or inflammation are important pathomechanism in the development of brain injury. As infections and subsequent inflammation are almost unavoidable on NICUs, new anti-inflammatory approaches are needed. In differend experimental settings, mesenchymal stem cells (MSCs) show these anti-inflammatory abilities. Although intravenously administered MSCs get trapped in the lung, therapeutic effects in target tissue are detectable, thereby indicating paracrine mechanisms. Since MSC-supernatants contain molecules with immunosuppressive functions, such as the identified TSG-6, we wondered whether MSC supernatants contain additional, maybe synergistically acting factors. The objective of this study is to evaluate the effect of concentrated MSC-supernatant on brain damage caused by inflammation. Methods: Wistar rats were randomized in 4 groups (vehicle/vehicle, vehicle/concentrated MSC-supernatant, LPS/vehicle, LPS/concentrated supernatant). LPS (0.25mg/kg) was administered at p3, concentrated MSC-supernatant at p3 and p4. At p5, animals were transcardially perfused, brains were removed and snap-frozen for molecularbiological analysis. Results: At p5, LPS-treated animals show a marked increase in apoptosis, whereas additional treatment with concentrated MSC-supernatant results in a decrease in neural apoptosis. Conclusions: Concentrated MSC-supernatant showed promising effects on inflammation-induced brain damage in an experimental model of encephalopathy of prematurity.